Produção, caracterização e aplicação de biossurfactante na remoção de óleo e na estabilização de nanopartículas de prata. - Silva, Bruna Gabryella Andrade de Lima (2023)
Biosurfactants are amphipathic molecules with great potential for application in various industrial sectors, due to their biochemical characteristics and because they are natural compounds with reduced toxicity, greater biodegradability and stability under adverse environmental conditions, compared to chemical surfactants. This work had as objective the production of biosurfactant by Candida lipolytica UCP 0988 and application in oil removal and stability of silver nanoparticles. The biosurfactant was produced in a medium containing 4.0% molasses, 2.5% cornstarch and 2.5% residual soybean oil, for 144 hours at 200rpm, after which the characterization, evaluation of stability, toxicity and application in oil removal. In the growth and biosurfactant production studies, the surface tension of the medium was reduced to 25 mN/m, Critical Micelle Concentration (CMC) of 0.5% and a yield of 12 g/L. Tests under extreme conditions of pH, temperature and NaCl indicated the stability of the biosurfactant. The chemical structures of the biosurfactant were identified by Infrared Spectroscopy and Magnetic Resonance, which revealed the glycolipidic nature. The anionic biosurfactant was not toxic to the microcrustacean Artemia salina or to vegetable seeds. The biosurfactant demonstrated efficiency in removing oil from sand, both in static and kinetic assays, at concentrations of 1/2CMC, 1xCMC and 2xCMC, showing 70-96% removal. The biosurfactant was also tested as a stabilizer in the synthesis of silver nanoparticles as an antimicrobial agent. Nanoparticles of size around 20 nm were obtained. The presence of the biosurfactant promoted stability, with a zeta potential of -60 mV being observed. The antimicrobial potential of AgNPs was evaluated against different microorganisms. Inhibition was observed for Staphylococcus aureus (90%), Echerichia coli (95%), Enterobacter (75.48%) and 70.67% inhibition for Pseudomonas aeruginosa, 90% for Candida albicans and 85% Aspergillus ninger at the concentration of 16.50 μg/mL AgNPs. The obtained results demonstrate that the Candida lipolytica biosurfactant has the potential to be used in several economic sectors, proving the biotechnological versatility of this biomolecule and its industrial importance.